Exploration of the Integration Development Path of Intelligent Companion Devices and Virtual Communities - Du, Ding (International Journal of Social Sciences and Public Administration, 2026)
With the aging population, the expansion of the solitary population, and the advancement of the digital society, intelligent companionship devices have shifted from single function devices to diversified service carriers. Virtual communities have become an important space to meet social needs and obtain emotional support. The integration of the two is not only an inevitable technological iteration, but also a key measure to respond to the upgrading of social service needs. This article combines the current status of technological development with practical demands, using literature research, logical analysis, and interdisciplinary perspectives to systematically explore the integration foundation, practical bottlenecks, technological support, scenario innovation, and guarantee mechanisms of the two. Research has found that integration requires technological interconnectivity as a prerequisite, scenario requirements as guidance, and security as the bottom line. By building unified technical standards, innovating service scenarios, and improving governance systems, it can achieve collaborative empowerment of "hardware terminals+digital communities". The research conclusion provides theoretical reference for the upgrading of the intelligent companionship industry and the expansion of virtual community functions, as well as practical paths for improving the accuracy and inclusiveness of digital social services.